Emerging antibody-based therapies for the treatment of acute myeloid leukemia. (July 2022) - Angenendt, Linus; Mikesch, Jan-Henrik; Schliemann, Christoph
Highlights: Antibody-based therapeutics have demonstrated substantial activity in AML. Combinations of antibodies with novel agents will hopefully be even more effective. Checkpoint inhibitors, bispecifics and immunocytokines open up a new avenue for the immunotherapy of AML. Abstract: The development of antibody-based therapeutics for patients with acute myeloid leukemia (AML) has long been hampered due to the shared expression of antigens on leukemic blasts and hematopoietic stem and progenitor cells (HSPC). Nevertheless, the first antibody-drug conjugate has been approved for the treatment of AML in the recent years. In addition, multiple antibody-based therapeutics including antibody-drug conjugates, bispecific antibodies and immunocytokines are currently being developed in clinical trials with some of them demonstrating encouraging results alone and/or in combination with current standard therapies. In this review we discuss current concepts of antibody-based therapies and results from emerging antibody-based therapeutics for the treatment of AML.